General Considerations in Sourcing Herbs, Spices and Agricultural Commodities in India - Ahluwalia, Sudhir (Biology, Engineering, Medicine and Science Reports)
India is one of the leading producers of herbs, spices and agricultural commodities. Pepper, cardamom, soybean, scented rice, wheat and nutraceutical ingredients in semi processed or fully processed forms are some of the key commodities exported from India to the Middle East, Asia Pacific region, Europe and the United States. To source efficiently from India, it is important to understand where these commodities are found, who grows them and how they are managed.1,2